Enhancing Critical Thinking Skills in Junior High School Students through the RADEC Learning Model on Vibration Material - Fatikhin, Achmad Choirul; Budiyanto, Mohammad; Qosyim, Ahmad (Jurnal Pijar Mipa, 2024)
In the rapidly evolving contemporary era, countries globally, including Indonesia, are compelled to adapt, with the Partnership for 21st Century Skills (P21) highlighting the crucial role of Critical Thinking, Creativity, Collaboration, and Communication (the 4Cs) for student success in the 21st century, yet traditional teacher-led learning often overlooks critical thinking skill development, contributing to low proficiency levels evident in assessments like the Programme for International Student Assessment (PISA). This study aims to describe the implementation of the Read, Answer, Discuss, Explain, and Create (RADEC) model on critical thinking skills in vibrations. The research design employed is descriptive through a one-group pretest-posttest design. The subjects of this study were 34 students in class VIII-A at SMP Negeri 54 Surabaya during the even semester of the academic year 2023/2024. Data collection techniques involved observation, tests, and questionnaires. Research instruments included learning implementation observation sheets, critical thinking skills tests, and student response questionnaires. The test results were analyzed using N-Gain and paired t-tests. The study's findings revealed that implementing the RADEC learning model on vibrations met the criteria very well, with a mode fully implemented. The student's critical thinking skills improved by an N-Gain analysis result of 0.38 and a paired t-test result of 0.000. The students also highly accepted the learning process using the RADEC model in the topic of vibrations, with 86% of statements strongly agreeing. Based on the description above, implementing the RADEC model can enhance students' critical thinking skills regarding vibrations.